Ferroptosis: a novel strategy to overcome chemoresistance in gynecological malignancies - Xu, Jing; Zheng, Bohao; Wang, Wei; Zhou, Shengtao (Frontiers in Cell and Developmental Biology, 2024)
Ferroptosis is an iron-dependent form of cell death, distinct from apoptosis, necrosis, and autophagy, and is characterized by altered iron homeostasis, reduced defense against oxidative stress, and increased lipid peroxidation. Extensive research has demonstrated that ferroptosis plays a crucial role in the treatment of gynecological malignancies, offering new strategies for cancer prevention and therapy. However, chemotherapy resistance poses an urgent challenge, significantly hindering therapeutic efficacy. Increasing evidence suggests that inducing ferroptosis can reverse tumor resistance to chemotherapy. This article reviews the mechanisms of ferroptosis and discusses its potential in reversing chemotherapy resistance in gynecological cancers. We summarized three critical pathways in regulating ferroptosis: the regulation of glutathione peroxidase 4 (GPX4), iron metabolism, and lipid peroxidation pathways, considering their prospects and challenges as strategies to reverse chemotherapy resistance. These studies provide a fresh perspective for future cancer treatment modalities.